2019
DOI: 10.1371/journal.pone.0211322
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of religiosity and association between religiosity and alcohol use, other drug use, and risky sexual behaviours among grade 8-10 learners in Western Cape, South Africa

Abstract: Background Alcohol and other drug use (AOD) and risky sexual behaviours remain high among adolescents in South Africa and globally. Religiosity influences, mitigates and provides resilience against engaging in risky behaviours among young people but few South African studies have explored potential associations between religiosity, AOD use and risky sex. We report the prevalence of religiosity and association between religiosity and AOD use and risky sexual behaviours among learners in the Western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
51
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 49 publications
(59 reference statements)
14
51
1
9
Order By: Relevance
“…While participants listed several activities, such as spending time with friends and family, volunteering, and arts and music, two activity categories arose as most salient: sports/exercise and religious activities. These specific categories are consistent with research describing the role of religious activity, including associated spirituality and social support [70][71][72][73], and sports and exercise [74,75] in supporting recovery from problematic substance use. Furthermore, these reflect the reinforcing, substance-free activities listed in qualitative interviews among a population with problematic substance use in a South African HIV care setting [44], indicating the potential role of these activities in BA for problematic substance use across cultures.…”
Section: Discussionsupporting
confidence: 81%
“…While participants listed several activities, such as spending time with friends and family, volunteering, and arts and music, two activity categories arose as most salient: sports/exercise and religious activities. These specific categories are consistent with research describing the role of religious activity, including associated spirituality and social support [70][71][72][73], and sports and exercise [74,75] in supporting recovery from problematic substance use. Furthermore, these reflect the reinforcing, substance-free activities listed in qualitative interviews among a population with problematic substance use in a South African HIV care setting [44], indicating the potential role of these activities in BA for problematic substance use across cultures.…”
Section: Discussionsupporting
confidence: 81%
“…Fourth, the study is cross-sectional, so we cannot determine a cause-effect relationship between risk factors and SRH behaviours of SIYP in the study populations. Finally, although the Nigeria population is highly religious, we did not measure the possible moderating effect of religiosity on our findings, which is a defect because religiosity moderates SRH behaviour [48,49].…”
Section: Discussionmentioning
confidence: 96%
“…Religiosity influence social interactions within social group by preventing behaviour that are harmful to health, such as alcohol and drugs and are also morally in society such as sex outside marriage (Francis et al, 2019). A study conducted by Andisti & Ritandiyono (2008) found that there was a significant relationship between religiosity and free sex behaviour, the higher religiosity, the lower the free sex behavior, and vice versa.…”
Section: Religiosity and Early Marriage Motivationmentioning
confidence: 99%